2017
DOI: 10.1007/s10936-017-9548-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Experience Norms for 506 Russian Nouns: Modality Rating, Spatial Localization, Manipulability, Imageability and Other Variables

Abstract: A number of new psycholinguistic variables has been proposed during the last years within embodied cognition framework: modality experience rating (i.e., relationship between words and images of a particular perceptive modality-visual, auditory, haptic etc.), manipulability (the necessity for an object to interact with human hands in order to perform its function), vertical spatial localization. However, it is not clear how these new variables are related to each other and to such traditional variables as imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 63 publications
12
35
0
2
Order By: Relevance
“…However, it slightly differs from previous work in Mandarin Chinese, where auditory words were found to be the less common together with olfactory words (Chen et al, 2019). The large distribution of visual information across words in our database is consistent with previous work on other languages like English (Lynott & Connell, 2009), Dutch (Speed and Majid, 2017), Russian (Miklashevsky, 2018), Mandarin Chinese (Chen et al, 2019) and Serbian (Đurđević et al, 2016). Overall, this crosslinguistic pattern provides support for the hypothesis that language semantics exhibits visual dominance in vocabulary usage and structure (Levinson & Majid, 2014;San Roque et al, 2015).…”
Section: Descriptive Statisticssupporting
confidence: 81%
See 1 more Smart Citation
“…However, it slightly differs from previous work in Mandarin Chinese, where auditory words were found to be the less common together with olfactory words (Chen et al, 2019). The large distribution of visual information across words in our database is consistent with previous work on other languages like English (Lynott & Connell, 2009), Dutch (Speed and Majid, 2017), Russian (Miklashevsky, 2018), Mandarin Chinese (Chen et al, 2019) and Serbian (Đurđević et al, 2016). Overall, this crosslinguistic pattern provides support for the hypothesis that language semantics exhibits visual dominance in vocabulary usage and structure (Levinson & Majid, 2014;San Roque et al, 2015).…”
Section: Descriptive Statisticssupporting
confidence: 81%
“…This pattern replicates a finding that emerged in previous similar studies using English, (Lynott and Connell,Figure 6: Spider plots illustrating the perceptual strength scores on the five senses for some example words, each of which is deemed representative of its class (vision unimodal for "bright", vision multimodal for "strange", audition unimodal for "silent", audition multimodal for "suave", touch for "soft", smell for "perfumed", taste for "disgusting" and abstract for "metaphysical"). ), Dutch (Speed & Majid, 2017), Mandarin Chinese (Chen et al, 2019) and Russian (Miklashevsky, 2018), uncovering an interesting cross-linguistic symmetry between Italian and these languages. The coupling of gustatory and olfactory experience in language semantics fits well within theories claiming that flavor perception can be considered as a unified, multisensory sense (e.g., Auvray & Spence, 2008).…”
Section: Descriptive Statisticsmentioning
confidence: 98%
“…In order to allow a more straightforward comparison among studies, we reported in Table 8 First, we demonstrated that our sample of words was experienced in a multimodal way. The multimodal composition of words has been supported by perceptual ratings of English adjectives, nouns and verbs Connell, 2009, 2013;Van Dantzig et al, 2011;Winter, 2016) and Dutch and Russian nouns (Speed and Majid, 2017;Miklashevsky, 2018). In line with previous norming ratings, we replicated a visual dominance effect Connell, 2009, 2013;Van Dantzig et al, 2011;Winter, 2016;Chen et al, 2019) with Italian speakers.…”
Section: Discussionsupporting
confidence: 87%
“…Following the original works by Connell on English (2009, 2013), perceptual strength norms have been also collected in different languages including Russian (Miklashevsky, 2018), Dutch (Speed and Majid, 2017), Mandarin (Chen et al, 2019). In order to allow a more straightforward comparison among studies, we reported in Table 8 First, we demonstrated that our sample of words was experienced in a multimodal way.…”
Section: Discussionmentioning
confidence: 99%
“…Since the original appearance of modality-specific norms of perceptual strength, interest in their broad utility has led other research groups to extend them in a variety of directions. Perceptual strength norms (also termed modality exclusivity norms, after the original Lynott & Connell, 2009, work) now exist in several different languages, including Russian (Miklashevsky, 2018), Serbian (Filipović Đurđević, Popović Stijačić, & Karapandžić, 2016, Dutch (Speed & Majid, 2017), and Mandarin (Chen, Zhao, Long, Lu, & Huang, 2019), and have been developed for concept-property pairs as well as individual words (van Dantzig, Cowell, Zeelenberg, & Pecher, 2011). The original English-language norms have also been applied in novel ways, such as examining stylistic differences of authors (Kernot, Bossomaier, & Bradbury, 2019), studying perceptual metaphors (e.g., rough sound, smooth melody; Winter, 2019), testing models of lexical representations (Johns & Jones, 2012), evaluating the iconicity of words in written (Winter, Perlman, Perry, & Lupyan, 2017), and signed languages (Perlman, Little, Thompson, & Thompson, 2018), and discovering links between sensory and emotional experience (Winter, 2016).…”
mentioning
confidence: 99%